Pendidikan dan Status Sosial sebagai Patokan Belis pada Perkawinan adat Manggarai di Desa Orong Kecamatan Welak Kabupaten Manggarai Barat - Jenau, Mariani Gonsia; Iswahyudi, Didik; Widijatmoko, Engelbertus Kukuh (LPPM Universitas Bina Bangsa, 2024)
A shift away from the belis-based traditional marriage system in Orong Village, Welak District, prompted this study. The changing meaning of belis impacts not only the character development of the community but also the economic burden on the community as a whole. In order to get a sociological understanding of the belis issue and the community's attempts to avoid it, this study will detail the Manggarai community belis's implementation in Orong Village, Welak District, West Manggarai Regency. To address an existing issue, this study will use a qualitative approach that describes data directly connected to society, institutions, and organizations. Through the use of in-depth interview methods and participatory observation, the existing data will be studied. The outcomes of the issue formulation above lead us to the conclusion that the Manggarai community's belis can be implemented by actively participating in the preservation of belis culture. In the meantime, we know the issue is belis because of the outcomes of the second formulation. The study's findings highlight the importance of education and social position in establishing belis worth. Belis' grades tend to rise in correlation with her level of education and social standing. The male family has not paid off the belief that the female family determined, so the marriage does not take place in the church. What's more, if the male family grows, it can be assumed that the woman has bought it so that she can treat him as she wants, which can lead to domestic violence (KDRT). Therefore, it is believed that future studies will be able to clarify the effect of high costs on household life